The Inspections problem in the network distribution of electricity: an evolutionary approach - Alan Bessa Gomes Peixoto (2015)
The planning of preventive maintenance is key role in the performance and quality of service of a power utility. The control of vegetation in the process of the electricity distribution network maintenance is of great importance to and continuous improvement of quality indicators of electricity supply, accompanied by the National Electric Energy Agency (ANEEL). The degree of criticality of pruning and productivity of teams are critical in this process. To resolve this issue it proposed a routing algorithm, in order to meet all the anomalies detected in previews, ensuring priority execution of critical cases within the period of maturity of the anomalies and before the occurrence of the failure. A genetic algorithm was developed and applied in solving this problem. The proposed technique has been adapted to a practical case of an electric utility and contributed a good economy and gains in productivity compared the current situation.